Age Related Changes in Central Corneal Thickness and Endothelial Cell Density - درويش تيم; يوسف حبيب; شحود هنادي (Latakia University Journal -Medical Sciences Series, 2020)
Purpose: To determine the influence of age on central corneal thickness (CCT), endothelial cell density (ECD), average cell area (MCA), coefficient of variation in cell size (CV), and percentage of regular hexagonal cells (EX). Methods: Specular microscopy was performed in (421) eyes of 220 healthy Syrian volunteers, they were divided by age into seven groups. Central corneal thickness (CCT), endothelial cell density (ECD), coefficient of variation (CV) in cell area, percentage of regular hexagonal cells (EX), average cell area (MCA) were studied. Results: A total of 113 (51.40%) women and 107 (48.60%) men participated in the study. Average ECD (cell/mm2) ranged from 2925±197.5 in 18-29 years old to 2280±13.1 in 80-87 years old. A strong inverse correlation was observed between age and corneal ECD (r = -0.9, p = 0.0001), CCT (μm) ranged from 566±21.6 in 18-29 years old to 548±6.04 in 80-87 years old. A weak inverse correlation was observed between age and CCT (r= - 0.2). There was also a statistically significant increase in CV and MCA with increasing age. There was also a statistically significant decrease in EX with age. There was no statistically significant difference in studied variables between genders. Conclusion: Central corneal thickness and endothelial cells density decreases significantly with age. The coefficient of variation and the mean cell size of the elderly increases, in contrast, the number of hexagonal cells decreases.